Analisis Kelayakan Ekonomi Tambang Batu Andesit PT. Batu Nago Mandiri Kecamatan Batang Kapeh, Kabupaten Pesisir Selatan, Provinsi Sumatera Barat - Hadyan Arif; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. PT. Batu Nago Mandiri is a company that will plan andesite miningin Batang Kapas districts, PesisirSelatan regency, province of West Sumatera. PT. Batu Nago Mandiri has a 52ha IUP area and has 23,750,000 tonsofandesite reserves and a mine life of 20 years. Parameter of organizing this research activity is seen in terms of theeconomy, estimation of tool needs and outcome sale of andesite stone. Therefore needed investment analysis and theeconomic feasibility of the mine to see the prospect of the andesite reserve whether it has economic value in that location.Then, the parameters used to determine economic viability in andesite production of PT. Batu Nago Mandiri is a NetPresent Value (NPV), Internal Rate Return (IRR), Payback Period (PBP).Based on the results of the economic analysisassessment, the Net Present Value valueis Rp. 1,632,077,494,690, 16% Internal Rate Return and 8-year Payback Period,the project is feasible to run. Estimated equipment requirements for Ore Getting requires 1 unit of Komatsu PC 400-LC8Excavator and 4 units of Hino 30T Dump Truck, while for Overburden Removal requires 1 unit of Komatsu PC300-8 MOExcavator and 3 units of Hino 30T Dump Truck. The income from the sale of andesite stones was Rp. 1,067,5000,000Keywords: Technical Economics, NPV, IRR, PBP, Estimated Equipment Requirement